2013
DOI: 10.1080/03079457.2013.800941
|View full text |Cite
|
Sign up to set email alerts
|

Changes of haematic parameters, redox status and mitochondrial complex activity in the heart and liver of broilers fed with different density diets under low ambient temperature

Abstract: This experiment was conducted to investigate the influence of dietary nutrient density on haematic parameters, oxidative status and mitochondrial complex activity in the heart and liver of broilers under low ambient temperature. Eight-day-old male ROSS-308 chickens were randomly divided into two treatments fed with normal (control) and high metabolizable energy (ME) and crude protein density (H) diets. A high nutrient density diet increased body weight gain and reduced the feed conversation ratio during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…In addition, a significant increase in the concentrations of MDA with a parallel decrease in activities of SOD, CAT, and GPx was observed in the plasma and liver tissue of the T3-treated birds, which is indicative of increased oxidative stress (Geng et al, 2004;Pan et al, 2005). These results support the previous findings, which showed higher generation of reactive oxygen intermediates (Iqbal et al, 2001;Arab et al, 2006), lower activity of enzymatic (Peng et al, 2013) and non-enzymatic (Nain et al, 2008) antioxidative systems, and elevated levels of oxidized lipids (Peng et al, 2013;Fathi et al, 2016) in broilers with naturally and experimentally induced ascites. Dietary supplementation of PP, especially at 3 g kg −1 , increased the liver activities of SOD, CAT, and GPx, and reduced the plasma and liver concentrations of MDA near to the control levels at 24 and 49 days of experiment.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a significant increase in the concentrations of MDA with a parallel decrease in activities of SOD, CAT, and GPx was observed in the plasma and liver tissue of the T3-treated birds, which is indicative of increased oxidative stress (Geng et al, 2004;Pan et al, 2005). These results support the previous findings, which showed higher generation of reactive oxygen intermediates (Iqbal et al, 2001;Arab et al, 2006), lower activity of enzymatic (Peng et al, 2013) and non-enzymatic (Nain et al, 2008) antioxidative systems, and elevated levels of oxidized lipids (Peng et al, 2013;Fathi et al, 2016) in broilers with naturally and experimentally induced ascites. Dietary supplementation of PP, especially at 3 g kg −1 , increased the liver activities of SOD, CAT, and GPx, and reduced the plasma and liver concentrations of MDA near to the control levels at 24 and 49 days of experiment.…”
Section: Discussionsupporting
confidence: 93%
“…At 21 and 35 days, the results showed that broilers in the model group had significantly higher HCT and AHI values, which were regarded as a threshold indicator of ascites and pulmonary hypertension. 33 The compensatory hyperplasia of the key organs resulted in a significant increase in the heart and liver index values in the model group compared with the control. In the histopathology examination, pulmonary artery remodeling was confirmed by the statistical analysis of RMT from different external diameters and microphotographs of pulmonary artery structures of the broilers' lungs, which were also regarded as typical parameters in the ascites syndrome.…”
Section: Discussionmentioning
confidence: 95%
“…Leading to induction of oxidative stress and ROS production (Pan et al, 2005). The increased ROS and enhanced nitric oxide synthase (NOS) expression and NO production have been previously reported in spontaneously hypertensive (Peng et al, 2013). The impaired NO synthesis in the heart ventricles has been also reported to be involved in the pathophysiology of cardiac failure in broilers chicken with PHS (Hasani et al, 2018).…”
Section: Discussionmentioning
confidence: 96%